Evaluation of the Unsteady Turbulence Modelling and Thermal Insulation on the Performance of Partial Combustion Lance - Law, Woon Phui; Jolius, Gimbun (AIDIC Servizi, 2015)
A computational fluid dynamics (CFD) study of a partial combustion lance (PCL) was performed using a hybrid scale adaptive simulation (SAS) in this work. In addition, the unsteady Reynolds-averaged NavierStokes(URANS) simulations using the standard k-ε (SKE), realizable k-ε (RKE) and renormalized (RNG)k-ε were performed for comparison purpose. Combustion was modelled using the species transport model, whereas the heat transfer was calculated using a combined convection-radiation boundary condition. Suitability of various gradient methods (i.e., Green-Gauss node-based, Green-Gauss cell-based and least squares cell-based) to discretize the convection and diffusion terms in the governing equations were assessed by comparing the CFD prediction with experimentally measured temperature. It was found that SAS provided a better prediction of the PCL temperature with about 5.1 % of error from the experimental data. The Green-Gauss node-based method showed a better agreement compared to the two cell-based gradient methods. Installation of thermal insulation increased the peak temperature by about 9.4 %. The finding in this work indicated that CFD model is useful for retrofitting study of an existing PCL.